2023
DOI: 10.3892/etm.2023.12125
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA and circRNA expression profiles in the hippocampus of Aβ25‑35‑induced AD mice treated with Tripterygium glycoside

Abstract: Tripterygium glycosides (TG) have been reported to ameliorate Alzheimer's disease (AD), although the mechanism involved remains to be determined. In the present study, the lncRNA and circRNA expression profiles of an AD mouse model treated with TG were assessed using microarrays. lncRNAs, mRNAs, and circRNAs in the hippocampi of 3 AD+normal saline (NS) mice and 3 AD+TG mice were detected using microarrays. The most differentially expressed lncRNAs, mRNAs, and circRNAs were screened between the AD+NS and AD+TG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 65 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…For instance, prior research has revealed that overexpression of bcl1 by miRNAs increases the effectiveness of autophagy while also inhibiting apoptosis. 30,129 Therefore, it is crucial to have a deeper knowledge of how miRNA regulates autophagy to fully comprehend the development of PD. In addition, these neurotoxic miRNAs may impact the course of PD via many targets.…”
Section: Ta B L Ementioning
confidence: 99%
“…For instance, prior research has revealed that overexpression of bcl1 by miRNAs increases the effectiveness of autophagy while also inhibiting apoptosis. 30,129 Therefore, it is crucial to have a deeper knowledge of how miRNA regulates autophagy to fully comprehend the development of PD. In addition, these neurotoxic miRNAs may impact the course of PD via many targets.…”
Section: Ta B L Ementioning
confidence: 99%
“…One important area that has been extensively explored is the regulation of RNA expression [ [109] , [110] , [111] , [112] , [113] ]. Through meticulous investigations, researchers have elucidated the intricate mechanisms governing the control and modulation of RNA expression, unravelling the complex interplay between transcriptional and post-transcriptional processes [ 114 ]. Some studies mentioned above have significantly contributed to our understanding of nanocrystalline materials and their applications in various fields.…”
Section: Stimulation Of Sc Production Through Exercisementioning
confidence: 99%
“…Dementia-related diseases can be caused by genetic regulators, particularly non-coding RNAs (ncRNAs) such as microRNA (miRNA), long non-coding RNA (lncRNA), and circular RNA (circRNA) [ 22 , 23 ]. MiRNA, a small ncRNA of about 20 nucleotides, regulates its target gene by binding complementarily to the 3′ untranslated region (UTR) of the gene [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%